Characterization of covalent protein modification by triclosan in vivo and in vitro via three-dimensional liquid chromatography-mass spectrometry: New insight into its adverse effects. (March 2020) - Liu, Meixian; Li, Na; Zhang, Yida; Zheng, Zhiyuan; Zhuo, Yue; Sun, Baoqing; Bai, Li-Ping; Zhang, Mingming; Guo, Ming-Quan; Wu, Jian-Lin
Graphical abstract: Highlights: A 3D-LC-MS-based proteomics method was developed to detect trace proteins in serum. Triclosan (TCS) metabolites could covalently bind to proteins via cysteine residues. 45 proteins were found to be modified by TCS metabolites in rats. Modified proteins were found to be related with TCS-induced adverse effects. Covalent protein modification is a possible reason of TCS-induced adverse effects. Abstract: Triclosan (TCS), an antimicrobial agent widely used in personal care products and ubiquitously exists in environment, has drawn increasing concern due to its potential to exert multiple adverse effects, ranging from endocrine disruption to carcinogenesis. However, the mechanism of these adverse effects is still not fully elucidated. More and more studies have shown that chemical reactive metabolites (RMs) covalently binding to proteins is a possible reason for these adverse effects, but there is still a lack of appropriate methods to predict or evaluate these adverse effects due to the extremely low abundance of the modified proteins in complex biological samples. In this study, we attempted to address this problem and investigate the possible mechanism of TCS adverse effects by a shotgun proteomics approach based on three-dimensional-liquid chromatography-mass spectrometry (3D-LC-MS). First, the in vitro incubation with model amino acids and protein in microsomes showed that TCS could react with cysteine residue of proteins through 3 types of RMs. Then, a 3D-LC-MS approach was developed to sensitively determine the low abundant modified proteins, which resulted in the identification of 45 TCS-modified proteins, including albumin, haptoglobin and NR1I2, in rats. STRING analysis indicated that these modified proteins mainly were involved in reproductive and development system, endocrine and immune system, and carcinogenesis, which were in accord with the main reported TCS-induced adverse effects and suggested that the covalent modification of TCS RMs for proteins might affect their activities and functions, thus inducing serious adverse effects. This study provided a new insight into the mechanism of TCS adverse effects and may serve as a valuable method to predict or evaluate adverse effects of ubiquitous chemicals.